Immunometabolism: Towards a Better Understanding the Mechanism of Parasitic Infection and Immunity - Chen, Jing-yue; Zhou, Ji-kai; Pan, Wei (Frontiers in Immunology, 2021)
As a relatively successful pathogen, several parasites can establish long-term infection in host. This “harmonious symbiosis” status relies on the “precise” manipulation of host immunity and metabolism, however, the underlying mechanism is still largely elusive. Immunometabolism is an emerging crossed subject in recent years. It mainly discusses the regulatory mechanism of metabolic changes on reprogramming the key transcriptional and post-transcriptional events related to immune cell activation and effect, which provides a novel insight for understanding how parasites regulate the infection and immunity in hosts. The present study reviewed the current research progress on metabolic reprogramming mechanism exploited by parasites to modulate the function in various immune cells, highlighting the future exploitation of key metabolites or metabolic events to clarify the underlying mechanism of anti-parasite immunity and design novel intervention strategies against parasitic infection.